2023
DOI: 10.3390/ijms242216159
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nasal Nitric Oxide in Primary Ciliary Dyskinesia and Other Respiratory Conditions in Children

Salvatore Paternò,
Laura Pisani,
Stefania Zanconato
et al.

Abstract: Nitric oxide (NO) is produced within the airways and released with exhalation. Nasal NO (nNO) can be measured in a non-invasive way, with different devices and techniques according to the age and cooperation of the patients. Here, we conducted a narrative review of the literature to examine the relationship between nNO and some respiratory diseases with a particular focus on primary ciliary dyskinesia (PCD). A total of 115 papers were assessed, and 50 were eventually included in the review. nNO in PCD is low (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 53 publications
1
0
0
Order By: Relevance
“…In these cells, NO regulates ciliary beating frequency via cAMP and cGMP. Thus, cAMP and cGMP activate protein kinases A and G, which phosphorylate dynein light chains, increasing ciliary beating, which is deficient in PCD patients [19]. Our results agree with these previous reports and support the hypothesis that the low nNO levels observed in PCD patients are due to a decreased biosynthesis of the molecule since, at the cellular level, we have observed that these levels are significantly lower.…”
supporting
confidence: 92%
“…In these cells, NO regulates ciliary beating frequency via cAMP and cGMP. Thus, cAMP and cGMP activate protein kinases A and G, which phosphorylate dynein light chains, increasing ciliary beating, which is deficient in PCD patients [19]. Our results agree with these previous reports and support the hypothesis that the low nNO levels observed in PCD patients are due to a decreased biosynthesis of the molecule since, at the cellular level, we have observed that these levels are significantly lower.…”
supporting
confidence: 92%